Postoperative washing of sutured wounds. (November 2016) - Harrison, Conrad; Wade, Cian; Gore, Sinclair
Abstract: A best evidence topic was written according to the structured protocol. The three part question addressed was: [In patients undergoing closure of surgical wounds with sutures] does [keeping the wound dry for the first 48 h after closure] [reduce the incidence of surgical site infections (SSIs)]? 4 relevant papers were culled from the literature and appraised. The authors, date, country, population, study type, main outcomes, key results and study weaknesses were tabulated. Current NICE guidelines recommend cleaning surgical wounds with sterile saline only for the first 48 h following skin closure. We found no evidence that washing wounds with tap water during this period increases the incidence of SSIs compared to keeping them dry. Further randomised controlled trials will enable the construction of conclusive systematic reviews and meta-analyses. Highlights: A best evidence topic was conducted according to the standard protocol. Best available evidence shows no advantage of keeping surgical wounds dry in the first 48 h. More RCTs are needed before conclusive meta-analyses can be constructed.